DEGRADATION DUE TO GOLD EXPLORATION IN THE CAXIAS MINE, LUÍS DOMINGUES – MA - Lílian Daniele Pantoja Gonçalves; Marcia Silva Furtado; José Fernando Rodrigues Bezerra; Lívia Cândice Ribeiro Silva; Lenir Cardoso Brito; Antonio Cordeiro Feitosa (Sociedade & Natureza)
The gold is one of few metals that exist in the nature in natural state, showing natural brightness and great beauty. For these features it is supposed to be the first metal to call the attention from primitive man about 20.000 years ago. This mineral is supposed to be the first metal, whose importance was recognized by the human being, but its use only was possible in the Bronze Age, with the development of the foundry art.The actions that result from the mining demonstrate a degradation environmental feature bigger than what seem, because, when it is practiced in a disordered way and with low technologic control, it is a negative aspect because of the environmental devastation that occurs.It is undeniable that, in a modern world, the mining in general has decisive importance for the economic progress and development, since the mining mineral of the nature are present in almost all manufactured goods, and this generate the human dependence on the minerals. However, this dependence implies charges to the society by the development of huge degraded areas, which after the exploration, most time, cannot be occupied or explorated economicallly.